Case series of progressive familial intrahepatic cholestasis type 3: Characterization of variants in ABCB4 in China - Cheng, Jinlin; Gong, Ling; Mi, Xiaoxiao; Wu, Xiangyan; Zheng, Jun; Yang, Wenjun (Frontiers in Medicine, 2022)
Objective: To improve the accuracy of the diagnosis of familial progressive intrahepatic cholestasis type 3 (PFIC3, https://www.omim.org/entry/602347) Method: Between September 2019 and March 2021, we recruited four patients with PFIC3 from two liver centers in East China. Molecular genetic findings of ATP-binding cassette subfamily B member 4 (ABCB4, https://www.omim.org/entry/171060) were prospectively examined, and clinical records, laboratory readouts, and macroscopic and microscopic appearances of the liver were analyzed. Results: Four patients experienced cholestasis, mild jaundice, and elevated levels of serum direct bilirubin, γ-glutamyltransferase, or total bile acids. All patients had moderate-to-severe liver fibrosis or biliary cirrhosis, and their liver biopsy specimens stained positive with rhodamine. Molecular immunohistochemistry revealed reduced or absent MDR3 expression in all liver specimens. A novel mutation of ABCB4 (c.1560+2T>A) was identified in patients with PFIC3, which is of high clinical significance and may help understand mutant ABCB4 pathogenesis. Conclusions: MDR3 immunohistochemistry and molecular genetic analyses of ABCB4 are essential for the accurate diagnosis of PFIC3.